Paediatric high‐flow nasal cannula therapy in children with bronchiolitis: A retrospective safety and efficacy study in a non‐tertiary environment. (April 2017) - Davison, Michelle; Watson, Mike; Wockner, Leesa; Kinnear, Frances
Abstract: Objective: The objective was to examine the safety and efficacy of high‐flow nasal cannula (HFNC) therapy for children with bronchiolitis in a non‐tertiary paediatric setting. Methods: This was a single‐centre retrospective study conducted over 26 months (March 2013–April 2015) on children aged 1–23 months with suspected bronchiolitis, who commenced on HFNC therapy in either the ED or the ward. Changes with respect to baseline data were analysed for effect on work of breathing (WOB), heart rate (HR) and respiratory rate (RR). Data was analysed using a linear mixed effects model and adjusted for age (≤12 months and >12 months) and location (ED vs ward). Transfer to a tertiary environment, escalation of care and adverse event rates were also recorded. Results: A total of 61 children commenced on HFNC therapy, with flow rates ranging from 0.6 to 3.3L/kg/min. The proportion of patients with higher WOB scores appeared to reduce within 60 min of initiation of therapy. There was also a progressive reduction in surrogate markers of respiratory distress (HR and RR), with significant reductions evident by 60 min ( P < 0.05). There were no adverse events related to HFNC therapy. The transfer rate was 13%. It was predominantly due to lack of improvement of physiological parameters post initiation of HFNC therapy. None of the transferred patients required escalation of care. Conclusion: Within the limitations of this study it appears HFNC therapy may be safely commenced in both age groups in a non‐tertiary ED or ward, with an appropriate level of observation and robust transfer criteria.